Modeling QTL-by-environment interactions for multi-parent populations - Li, Wenhao; Boer, Martin P.; Joosen, Ronny V. L.; Zheng, Chaozhi; Percival-Alwyn, Lawrence; Cockram, James; Van Eeuwijk, Fred A. (Frontiers in Plant Science, 2024)
Multi-parent populations (MPPs) are attractive for genetic and breeding studies because they combine genetic diversity with an easy-to-control population structure. Most methods for mapping QTLs in MPPs focus on the detection of QTLs in single environments. Little attention has been given to mapping QTLs in multi-environment trials (METs) and to detecting and modelling QTL-byenvironment interactions (QEIs). We present mixed model approaches for the detection and modelling of consistent versus environment dependent QTLs, i.e., QTL-by-Environment Interaction (QEI). QTL effects are assumed to be normally distributed with variances expressing consistency or dependence on environments and families. The entries of the corresponding design matrices are functions of identity-by-descent (IBD) probabilities between parents and offspring and follow from the parental origin of offspring DNA. A polygenic effect is added to the models to account for background genetic variation. We illustrate the wide applicability of our method by analyzing several public MPP datasets with observations from METs. The examples include diallel, nested association mapping (NAM), and multi-parent advanced inter-cross (MAGIC) populations. The results of our approach compare favorably to those of previous studies that used tailored methods.